2020
DOI: 10.1111/jphp.13344
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of therapeutic approaches available for the treatment of cholera

Abstract: Objectives The oral rehydration solution is the most efficient method to treat cholera; however, it does not interfere in the action mechanism of the main virulence factor produced by Vibrio cholerae, the cholera toxin (CT), and this disease still stands out as a problem for human health worldwide. This review aimed to describe therapeutic alternatives available in the literature, especially those related to the search for molecules acting upon the physiopathology of cholera. Key findings New molecules have of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 138 publications
0
4
0
2
Order By: Relevance
“…O tratamento envolve a reidratação oral ou intravenosa para substituir os fluidos e eletrólitos perdidos, além do uso de antibióticos em casos graves (SOUSA et al, 2020). A prevenção da cólera é baseada na melhoria do saneamento, acesso à água potável e educação sobre higiene (ALI et al, 2015).…”
Section: Coléraunclassified
“…O tratamento envolve a reidratação oral ou intravenosa para substituir os fluidos e eletrólitos perdidos, além do uso de antibióticos em casos graves (SOUSA et al, 2020). A prevenção da cólera é baseada na melhoria do saneamento, acesso à água potável e educação sobre higiene (ALI et al, 2015).…”
Section: Coléraunclassified
“…Studies conducted in infant mice and rabbits found that a combination of three isolated V. cholerae-specific virulent phages (ICP1, ICP2, and ICP3) was able to decrease the bacterial load of V. cholerae and prevent cholera-like diarrhea (91). Experimental studies targeting the inhibitor of cystic fibrosis channel transmembrane (CFTR), inhibitors of virulence factors, and a monosialoganglioside (GM1) antagonist found that they reduced intestinal secretion induced by CT of V. cholerae (92).…”
Section: Future Treatmentsmentioning
confidence: 99%
“…The core mechanism by which Vibro cholorae initiates disease, which is responsible for the dehydration observed during cholera, is the secretion of CT, which is a protein complex [7][8][9][10]. After colonization by Vibrio cholorae, the bacteria secrete cholera enterotoxin, which interacts with the receptors in the intestinal epithelium, thereby leading to the manifestation of the symptoms mentioned earlier [11]. Studies have shown that a wide range of treatment options, including oral rehydration therapy, the use of antimicrobial agents, antibiotics and vaccines, are available, each of which depends on the severity of the patient's cholera [11].…”
Section: Introductionmentioning
confidence: 99%
“…After colonization by Vibrio cholorae, the bacteria secrete cholera enterotoxin, which interacts with the receptors in the intestinal epithelium, thereby leading to the manifestation of the symptoms mentioned earlier [11]. Studies have shown that a wide range of treatment options, including oral rehydration therapy, the use of antimicrobial agents, antibiotics and vaccines, are available, each of which depends on the severity of the patient's cholera [11]. However, due to the development of new antibiotic-resistant strains of Vibrio cholerae, there is a need to develop more treatment options.…”
Section: Introductionmentioning
confidence: 99%